2006
DOI: 10.1162/108819806775545411
|View full text |Cite
|
Sign up to set email alerts
|

Industrial Symbiosis in Kalundborg, Denmark: A Quantitative Assessment of Economic and Environmental Aspects

Abstract: As a subdiscipline of industrial ecology, industrial symbiosis is concerned with resource optimization among colocated companies. The industrial symbiosis complex in Kalundborg, Denmark is the seminal example of industrial symbiosis in the industrial ecology literature. In spite of this, there has been no in‐depth quantitative analysis enabling more comprehensive understanding of economic and environmental performances connected to this case. In this article some of the central industrial symbiotic exchanges, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
327
0
29

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 612 publications
(359 citation statements)
references
References 23 publications
3
327
0
29
Order By: Relevance
“…emission of other gasses including green-house-gasses (GHG) in general or health effects and social perception) and effectiveness in IS practice, and along some previous studies (Chertow, Lombardi 2005, Jacobsen 2006b, Martin, Eklund 2011, Martin et al 2012, Mattila et al 2012) and current practice in IS . Still, the proposed framework allows for further expansion.…”
Section: Figure 10 Is Environmental Metricsmentioning
confidence: 92%
See 1 more Smart Citation
“…emission of other gasses including green-house-gasses (GHG) in general or health effects and social perception) and effectiveness in IS practice, and along some previous studies (Chertow, Lombardi 2005, Jacobsen 2006b, Martin, Eklund 2011, Martin et al 2012, Mattila et al 2012) and current practice in IS . Still, the proposed framework allows for further expansion.…”
Section: Figure 10 Is Environmental Metricsmentioning
confidence: 92%
“…Although the practice of IS has demonstrated the need for evaluating these benefits either in the process of screening of impending options or monitoring the operation of symbiotic networks, and despite of some attempts to quantify them ( Van Berkel 2010, Mattila, Pakarinen & Sokka 2010, Berkel et al 2009), no unified metrics or methods for calculating concomitant indicators has been proposed (Eckelman, Chertow 2009, Jacobsen 2006a). Consequently, evaluation of IS networks performance has been identified as deficient (Martin et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Use of treated wastewater as cooling water at the power station avoids effluent discharges of some 161 ML/day and saves at least USD 425 000/year. • In Kalundborg (Denmark (27)) three main water exchanges have substituted 2.8 GL/year groundwater with surface water and subsequently achieved 0.5 GL/ year conservation of surface water with operational savings of some 27.6 million DKK (∼3.5 million USD/ year). The supply of waste heat as steam, hot water, and cooling water for various applications realizes a saving of 1.3 million GJ/year compared to stand-alone heat production.…”
Section: Introductionmentioning
confidence: 99%
“…As a sub-discipline of IE, Industrial Symbiosis is concerned with resource optimization among collocated companies (Jacobsen 2006). Industrial Symbiosis brings together traditionally separate industries into a collective approach for competitive advantage involving physical exchange of materials, energy, water, and/or by-products (Chertow 2000).…”
mentioning
confidence: 99%
“…Results have shown that significant environmental savings are related to Industrial Symbiosis in Kalundborg (Jacobsen 2006). For example, three million m 3 of water could be saved through recycling and reuse.…”
mentioning
confidence: 99%